IMPROVING STUDENTS’ QUESTIONING ABILITY THROUGH LITERACY IN NARRATIVE TEXT USING PROBLEM-BASED LEARNING - MISAI, NABELDA TAUFIKA (Universitas Islam Nahdlatul Ulama Jepara, 2023)
This study aims to improve students' questioning ability in narrative text learning through the application of literacy in narrative text using problem-based learning. The research method used is classroom action research with planning, implementation, reflection, and action steps. The research sample is 34 grade 11 students from SMA Negeri 9 Malang, and questioning skills are measured based on quantity and quality indicators of questions that refer to Bloom's taxonomy. Data used are observation data and question results from the pre-test and post-test. The research instruments used are observation sheets, pre-test, and post-test. Data analysis was conducted quantitatively using percentages through Microsoft Excel which will then be explained using descriptive interpretation. This study successfully increased student question quantity by 61% in cycle I and 72% in cycle II, as well as improved student question quality at levels C3, C4, and C5 in cycle II. In addition, there was an increase in students' cognitive levels in the second cycle, especially at levels C1 and C2. Based on the research results, it can be concluded that Literacy in Narrative Text Using a Problem-Based Learning method is effective in improving students' questioning ability in narrative text learning.